Online food delivery services and unceasing behavioural intention: An assessment for integrating expectation-confirmation and technology acceptance models - Mussina, Kamshat; Podsukhina, Olga; Omarova, Kenzhegul; Rustemova, Sabira; Shaimova, Aigerim; Tleuberdiyeva, Saltanat (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
The coronavirus disease (COVID-19) quarantine restrictions led to significant changes in the food industry's delivery methods, with a notable rise in online food delivery services (OFDS). This increase necessitates a deeper understanding of the factors influencing the continued use of these services. This study investigates the relationships between perceived ease of use, perceived usefulness, satisfaction, confidence, trust, and continuous intention to use OFDS applications among young consumers in Kazakhstan. An integrated model based on expectation-confirmation and technology acceptance models, incorporating the habit of online shopping as a moderator, was used. Data was collected from 433 respondents with prior OFDS experience and analyzed using Smart PLS 4.0. The results show positive correlations between perceived ease of use, perceived usefulness, satisfaction, confidence, trust, and the continuous intention to use OFDS among young Kazakhstani consumers. Additionally, the study confirms the moderating role of online shopping habits in the relationship between satisfaction and trust and the continuous intention to use OFDS. These findings offer valuable insights for companies in the online food delivery sector, highlighting key factors that can enhance managerial and IT strategies to boost revenues and foster sustained use of OFDS applications.